FORMATION AND USE OF RETURNED FUNDS IN THE SYSTEM OF MANAGEMENT OF THE FINANCIAL STATE OF THE ENTERPRISE - MAZUR, Dmytro; MAZUR, Oleksandr; MAZUR, Galina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the current state of formation and use of working capital in the system of managing the company’s financial condition. The essence of the efficiency of the use of working capital is disclosed and how the company’s liquidity, its financial stability, solvency and profitability depend on them. The principled approaches to the formation of the company’s current assets are illustrated. Different ratios of the level of efficiency and the risk of using working capital are shown. The structure of current assets was determined by accelerating their activity. Ways of improving working capital for the introduction of modern technologies and other achievements of scientific and technological progress are considered. Planned needs for working capital have been determined, which provide for the development of relatively long-term norms and norms for a specific period. Management of working capital is considered as a component of financial management. The goals and objectives of the formation of working capital and their coordination with the strategic goals of the enterprise are determined. The basic policy and methods of working capital management in terms of its individual components are disclosed. The composition and structure of working capital has been formed. A mechanism for managing working capital components has been developed. The amount and structure of current assets, the sources of their coverage and the ratio between them, sufficient to ensure the long-term production and efficient financial activity of the enterprise, are determined. The model of the circulation of capital of the enterprise is considered. The formula for calculating the duration of an enterprise’s operating cycle has been determined. A scheme of the production and financial cycles of the circulation of the working capital of the enterprise has been developed. A working capital management policy has been formed. The structure of current assets has been optimized.